Coordinated development of shale gas benefit exploitation and ecological environmental conservation in China: a mini review - Li, Hu (Frontiers in Ecology and Evolution, 2023)
Drawing from the successful exploration and development of shale gas in the Sichuan Basin, this paper employs a bibliometric approach and utilizes the Web of Science database as its data source to review the impact of shale gas development on the ecological environment. Furthermore, effective strategies for achieving coordinated development of shale gas benefit exploitation and ecological environmental conservation in China are identified. The findings highlight that the ecological impact of shale gas development has been a major focus of research over the past decade, primarily involving concerns such as water resources consumption, groundwater pollution, methane emissions, and waste management. These challenges can be addressed by adopting measures such as responsible water usage, maintaining well integrity, proper storage and disposal of fracturing flowback fluids, and appropriate management of drilling solid waste. The key to achieving green and efficient shale gas development in China lies in constructing a solid theoretical framework for benefit exploitation, refining environmental management standards and regulations, and promoting the development of clean production technologies specific to shale gas. Additionally, establishing a distinct exploration and development theory and fostering technical innovation for deep shale gas (buried depth > 3500m) are pivotal for enhancing and stabilizing production in China. Clarifying the theoretical logic of benefit development and improving the environmental protection law of shale gas development are of great significance for realizing the scale benefit development of shale gas and the harmonious development of ecological environment in China.